Understanding the mechanism of action of pyrrolo[3, 2-b]quinoxaline-derivatives as kinase inhibitors. Issue 6 (19th May 2020) - Unzue, Andrea; Jessen-Trefzer, Claudia; Spiliotopoulos, Dimitrios; Gaudio, Eugenio; Tarantelli, Chiara; Dong, Jing; Zhao, Hongtao; Pachmayr, Johanna; Zahler, Stefan; Bernasconi, Elena; Sartori, Giulio; Cascione, Luciano; et al.
Abstract : Two novel quinoxaline-based EphA3 tyrosine kinase inhibitors have been designed and characterized in vivo in a relevant lymphoma model, showing high efficacy in the control of tumor size. Abstract : The X-ray structure of the catalytic domain of the EphA3 tyrosine kinase in complex with a previously reported type II inhibitor was used to design two novel quinoxaline derivatives, inspired by kinase inhibitors that have reached clinical development. These two new compounds were characterized by an array of cell-based assays and gene expression profiling experiments. A global chemical proteomics approach was used to generate the drug-protein interaction profile, which suggested suitable therapeutic indications. Both inhibitors, studied in the context of angiogenesis and in vivo in a relevant lymphoma model, showed high efficacy in the control of tumor size.